Smart Manufacturing through TOC based Efficiency Monitoring System (TBEMS) - V, Balaji; Venkumar, P.; MS, Sabitha (International Journal of Engineering and Technology, 2018)
The very purpose of business is to devise profitability and enhance it in all possible avenues sustainable. In a manufacturing environment, thus, there had been a number of techniques and concepts adapted to improvise the effectiveness thereby profits continuously. Theory of Constraints (TOC) adopts a unique con-cept exploiting the constraint to deliver the customer needs. TOC is built on the premise that the weakest link determines the strength of the whole chain. With the advent of Industry 4.0, the manufacturing systems could be exploited to the next best level, leveraging the interaction of cyber physical systems and human beings over the internet. This paper deals with a novel idea of implementing TOC concept blended with Internet of Things (IoT), thereby, the speed of implementation could be augmented for early results. Evidently, the smartness of Things is    derived based on the possibility of informed and proactive decisions.  Hence all the productivity improvement techniques and concepts could be complemented with such concurrent information and analytics, thereby the learning and decisions are much smarter and proactive. A real time industrial environment has been chosen to experiment this approach and the results are furnished paving way for future research and improvisation globally on the industrial environment and on many other competing productivity concepts